An Investigation to the Students’ Difficulties in the Skills of Reading Comprehension at TOEFL Proficiency Subject - Herman, Herman; Sinaga, Yanti Kristina; Simatupang, Gracia Elizabeth (CV. Creative Tugu Pena, 2024)
The objective of this study is to find out the difficulties faced by the students in the skill of reading comprehension at TOEFL Proficiency subject at the seventh semester of Universitas HKBP Nommensen Pematangsiantar. Descriptive qualitative approach was implemented in this research. Students of seventh semester from English Department in the academic year of 2023/2024 were as the subject of the research, and reading comprehension test as the object of the research. The researchers collected the data from the students’ final exam from their TOEFL subject. The result showed that there were some problems/difficulties faced by the students/participants after analysing the data and collected the interview from some participants, they were: 1) lack of vocabulary, 2) lack of time and losing focus in the reading comprehension, 3) unfamiliar text and lack of practising, and 4) lack of motivation. From the problems faced by the participants, the researchers also found the results of their test achievement were categorized as satisfied since 46,75% (36 students) got the score range 80-100. From the findings obtained, the researchers concluded that more practices need to be taken if the students/participants want to get a better result of the TOEFL test in the future. Keywords: Reading Comprehension, Reading Skill, TOEFL Proficiency